Optical fiber-based core-shell coaxially structured hybrid cells for self-powered nanosystems - Pan, Caofeng (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.